Implikasi Penetapan Usia Minimal Nikah Menurut Pasal 7 Undang-Undang No. 1 Tahun 1974 di Kabupaten Majene - Hasyim Hasyim (Al-Bayyinah, 2019)
This research was a field research. This study emphasized the implications in determining the age of marriage in Article 7 of Act No. 1 of 1974 concerning marriage. This study examined the causes of minimum marriage age and the impact. The nature of this research was qualitative, which examined the sources obtained in field studies. This study was focused to examine the minimum age of marriage in Majene Regency. The analysis used in this study is descriptive qualitative. The results of this study indicated that the cause of marriage age in Majene Regency is the role of parents, low educational level, culture, economy and environment. The implications of determining the minimum age for marriage have a negative impact on the biological and psychological aspects and have a broader chance for children to drop out of school.Keywords: Implication-Minimum Marriage Age-Mejene District.